Essays on foreign direct investment in Uganda - Ahmed, Kasule Twaha (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
For over 20 years, Uganda has been aggressively promoting herself as one of the best investment destinations in Sub Saharan Africa. In an effort to make the country very attractive to the foreign investors, the government has introduced a wide range of incentives to motivate the flow of FDI into the country. However, other than the fact that the incentives are very expensive to the poor economy, FDI has been faulted for outcompeting domestic investors and driving them out of business as well as perpetuating imbalances in regional development. All this while and despite these concerns, very little effort has been made to establish empirically how FDI affects the Ugandan economy. This thesis is an attempt to comprehensively examine FDI in Uganda. It investigates inward FDI to Uganda from four dimensions with each dimension appearing as an essay in the thesis. Essay one probes the determinants of FDI to the country. The second essay investigates the effect of FDI on Uganda's economic growth. Essay three is an inquiry into whether FDI crowds-out domestic investment in Uganda while the last essay is an assessment of the regional distribution of FDI in Uganda. Overall, a number of policy implications from the study can be identified; for example, there is value in promoting the country for more FDI based on the fact that FDI makes a positive and significant contribution to economic growth. From the crowding evidence, it may be helpful to apply preferential policies with respect to the different sectors. In order to achieve the objective of balanced national development, it might be necessary to introduce special incentives in the regions which are lagging behind, or the government may consider creating industrial parks in those regions as a way of redistributing agglomerative advantages which are essential for determining the regional location of new FDI firms.